Application of Artificial Neural Network (ANN) to Predict Soil Organic Matter Using Remote Sensing Data in Two Ecosystems - Ayoubi, Shamsollah; Shahri, Ahmahdreza Pilehvar; Karchegani, Parisa Mokhtari; Sahrawat, Kanwar L. (IntechOpen, 2011)
None